REVERSE LOGISTICS AS A TOOL FOR ECOLOGIZATION OF THE ECONOMY BASED ON THE SUSTAINABLE DEVELOPMENT CONCEPT (Transport systems and technologies, 2021)
The article discusses the issues of environmental management in logistics based on the concept of sustainable development through the introduction of environmental logistics. The problem of human survival in conditions of limited natural resources against the background of the deterioration of the natural conditions of human existence has led to the creation of the concept of sustainable development, which requires taking into account environmental and social factors in all spheres of human life. Logistics as a field of practice makes a negative contribution to the state of the environment. Highlighted the contour of ecological logistics in the framework of the concept of sustainable development. On the basis of the basic rules of logistics, the rules of ecology were formed, which reflect the need for ecologization of logistics. The evolution of the development of ecology is investigated, the features of the ecologization of logistics at each stage of the development of logistics are highlighted. Ecology has been actively developing in recent years and has several promising research areas, one of which is reverse logistics, which focuses on managing the reverse flows of material resources. The essence, tasks and place of reverse logistics in the hierarchy of environmentally oriented directions have been determined. The evolution of logistics chains corresponding to the stages of logistics development has been investigated. Closed logistic chains as the basis of reverse logistics are considered, the composition of the flows forming them is determined.
Keywords: ecologistics, reverse logistics, closed logistic chain, reverse material flow.